Groundwater and the Sustainable Development Goals (SDGs) - Chambel, António (2019)
Groundwater is an important part of the water cycle, but this don’t reflects at all in the indicators for the Sustainable Development Goals (SDGs) of the United Nations (UN). Facing some logistical issues in what relates to data gathering and data treatment, the indicators, used to monitor objectives defined by UN for all the 17 SDGs, must be, for the Inter-Agency and Expert Group on Sustainable Development Goal Indicators (IAEG-SDGs), reasonable maintained under 100 to be treatable and useful for all the UN member states. As always, groundwater, as the major part of the available freshwater resources on the world, but also as the less understood part of the same cycle, has been somehow forgotten. Our aim must be to turn groundwater a priority in the international decisions, documents and governance. An example is the SDGs, on its goal 6, Clean Water and Sanitation, dedicated to the topic “Ensure access to water and sanitation for all”, the following targets related with clean water are appointed: by 2030 to achieve universal and equitable access to safe and affordable drinking water for all, to improve water quality, to substantially increase water-use efficiency across all sectors and ensure sustainable withdrawals and supply of freshwater to address water scarcity, to implement integrated water resources management at all levels, including through transboundary cooperation, to expand international cooperation and capacity-building support to developing countries in water-related activities; by 2020, to protect and restore water-related ecosystems, including aquifers. There is also an indication to support and strengthen the participation of local communities in improving water and sanitation management. To accomplish these targets in what respects groundwater, more efforts must be done to indicate to the countries the kind of data that must be collected and analysed in order to inform better the state of our groundwater resources.